2019
DOI: 10.1177/2040622319838443
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab in inflammatory bowel disease

Abstract: Anti-tumor necrosis factor (TNF) therapy has revolutionized the medical treatment of the inflammatory bowel diseases (IBD), Crohn’s disease (CD), and ulcerative colitis. Twenty years ago, infliximab became the first anti-TNF agent approved for IBD. Data from randomized controlled trials, large observational cohort studies, postmarketing registries, and meta-analyses show that infliximab is a very effective treatment for moderate to severe IBD with a good safety profile. Infliximab has been also used to treat p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
66
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 99 publications
0
66
0
1
Order By: Relevance
“…Biological therapy has been used as a rescue treatment in those patients who have not responded to antibiotic therapy (74) . In a retrospective Belgian study that included 28 patients with refractory pouchitis treated with Infliximab 5 mg/kg every eight weeks, showed that 88% presented a clinical response at 10 weeks, which was maintained in 56% of patients at 20 weeks (75) .…”
Section: Chronic Pouchitismentioning
confidence: 99%
“…Biological therapy has been used as a rescue treatment in those patients who have not responded to antibiotic therapy (74) . In a retrospective Belgian study that included 28 patients with refractory pouchitis treated with Infliximab 5 mg/kg every eight weeks, showed that 88% presented a clinical response at 10 weeks, which was maintained in 56% of patients at 20 weeks (75) .…”
Section: Chronic Pouchitismentioning
confidence: 99%
“…97) exceeded 160 000 in 2013, and the number of IBD patients is increasing . Corticosteroids, 5‐aminosalicylic acid, immune modulators, such as thiopurine and methotrexate , biological drugs, and anti‐tumor necrosis factor (TNF) antibody are used for the treatment of IBD in both CD and UC patients. We previously reported that Swertia japonica extract and its main compound swertiamarine, and Atractylodes lancea rhizome extract and a volatile component β‐eudesmol stimulated gastric emptying and/or small intestine motility by inhibiting the dopamine D 2 and/or 5‐HT receptor .…”
Section: Introductionmentioning
confidence: 99%
“…This treatment option has several drawbacks that warrant the development of alternative treatments, such as high cost, severe potentially lethal side effects and the fact that up to 50% of patients do not respond or lose sensitivity to this treatment over time 1 .…”
Section: Introductionmentioning
confidence: 99%